Packaging Innovation through Design Thinking for Ready-to-Drink Coffee Products - Natalie; Hussein, Ananda Sabil (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to implement the Design Thinking method in the innovation and development of ready-to-drink (RTD) coffee product packaging at Yujonokohi to overcome sales stagnation and improve product competitiveness. Design/Methodology/Approach – This study employs a descriptive qualitative approach using the Design Thinking method, which consists of six stages: definition, research, interpretation, ideation, prototyping, and evaluation. Data were collected through observations, in-depth interviews with the owner of Yujonokohi and target consumers from Generations Y and Z, as well as document analysis. Findings – The results indicate that the Design Thinking approach can be applied to develop an innovative and functional RTD coffee packaging prototype that aligns with target consumer preferences. The proposed packaging design is expected to increase product value, enhance visual appeal, and support improved sales performance and competitiveness in the coffee industry. Originality/Value This research provides value by applying the Design Thinking method to develop an innovative and consumer-aligned packaging prototype for RTD coffee, offering a structured approach that can guide similar SMEs in enhancing product appeal and market performance.